The prospects of Sarawak handicrafts' market: the case of Artlier Gallery / Arrominy Hj Arabi - Hj Arabi, Arrominy (2000)
The aim of this study is to look at the prospects of Sarawak Handicrafts and also its market. In a way this study is to improve on the weaknesses and problems about the Sarawak Handicrafts in Kuching and to develop its marketing strategies. Problems arose when doing this study as the researcher faced problems in gathering information due to lack of responses from the tourists and also local people. Besides that time was very limited and a lot of expenses incurred in doing this study. As for the data, such as secondary data and primary data, more time is needed to look for these data as most of the data are not available and difficult to allocate. Upon doing this research study, the researcher found out that a lot of tourists coming to Sarawak are impressed by the Sarawak Handicrafts and they are willing to spend money on these products. They loved to see the decorations on the handicrafts shops. They know that Sarawak also has plenty to offer especially in terms of traditional arts and crafts, as in woodwork, potteries, textile products, etc.